Dinamika Kemandirian Mahasiswa Perantauan - Fauzia, Nadia; Asmaran, Asmaran; Komalasari, Shanty (Jurnal Al-Husna, 2020)
The purpose of this study is to discuss the dynamics of the independence of UIN Antasari Banjarmasin students and what factors are behind the independence of UIN Antasari Banjarmasin students. The reason is because overseas there are changes in conditions and situations, so that students who leave will experience dynamics of independence. This type of research is a qualitative descriptive research approach. Selection of subjects using purposive sampling technique, which is based on the characteristics of the subject in accordance with the research objectives to be carried out. The object of this research is the dynamics of independence, the subject is 5 overseas students. Data collection techniques using interviews and observations. Based on the results of research that overseas students of UIN Antasari Banjarmasin need a process to be independent in living their lives overseas. That is because overseas there has been a change. Factors that influence the dynamics of independence of overseas students at UIN Antasari Banjarmasin are factors of parenting style, the order of children in the family, age and the education system in schools.